Total plasma homocysteine, age, systolic blood pressure, and cognitive performance in older people. - Budge, M; De Jager, C; Hogervorst, E; Smith, A (2002)
OBJECTIVES: To investigate the relationship between total plasma homocysteine (tHcy) levels, blood pressure (BP) variables, renal function, and measures of cognitive performance in older people. DESIGN: Initial cross-sectional analysis of a prospective cohort. SETTING: United Kingdom (Oxfordshire) community sample. PARTICIPANTS: One hundred fifty-eight community-dwelling volunteers aged 60 to 91. MEASUREMENTS: Neuropsychological tests (Cambridge Examination for Mental Disorders of the Elderly-Cognitive Section (CAMCOG), Mini-Mental State Examination (MMSE), and Geriatric Depression Scale), biochemical studies (tHcy, serum folate, vitamin B12, and serum cystatin C), BP, and other vascular risk factors. RESULTS: tHcy, age, systolic BP (SBP), and CAMCOG performance were significantly interrelated. tHcy was negatively associated with total CAMCOG score independent of years of education, serum folate, vitamin B12, and cystatin C levels. Older participants with higher tHcy levels had lower CAMCOG scores-especially men aged 70 and older. Higher tHcy levels were associated with poorer performance on the memory and perception subscores of CAMCOG but not with the other cognitive subscales or MMSE score. SBP also demonstrated a significant negative association with total CAMCOG and MMSE scores. CONCLUSIONS: These results suggest independent associations between tHcy (modified by age and sex) and SBP and cognitive performance in older people. Further longitudinal study will define whether optimization of tHcy and systolic BP contributes to the maintenance of cognitive performance with successful aging.